Underlying-event properties in pp and p-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kroesen, Martin; López, Jorge; Nath, Abhishek; Pachmayer, Yvonne C.; et al. (Journal of high energy physics, 2023)
We report about the properties of the underlying event measured with ALICE at the LHC in pp and p-Pb collisions at √sNN=5.02 Te. The event activity, quantified by charged-particle number and summed-pT densities, is measured as a function of the leading-particle transverse momentum (Pt trig). These quantities are studied in three azimuthal-angle regions relative to the leading particle in the event: toward, away, and transverse. Results are presented for three different pT thresholds (0.15, 0.5 and 1 GeV/c) at mid-pseudorapidity (|η| < 0.8). The event activity in the transverse region, which is the most sensitive to the underlying event, exhibits similar behaviour in both pp and p-Pb collisions, namely, a steep increase with pTtrig for low pTtrig, followed by a saturation at pTtrig ≈ 5 GeV/c. The results from pp collisions are compared with existing measurements at other centre-of-mass energies. The quantities in the toward and away regions are also analyzed after the subtraction of the contribution measured in the transverse region. The remaining jet-like particle densities are consistent in pp and p-Pb collisions for pTtrig >10 GeV/c, whereas for lower pTtrig values the event activity is slightly higher in p-Pb than in pp collisions. The measurements are compared with predictions from the PYTHIA 8 and EPOS LHC Monte Carlo event generators.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
The ALICE collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, M.C. Danisch, V.J.G. Feuillard, S. Fokin, P. Glässel, M. Kroesen, J. Lopez, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, G. Skorodumovs, J. Stachel, S. Stiefelmaier, C.A. van Veen, M. Völkl, B. Windelband, A. Yüncü, F. Zanone [und viele weitere]
Gesehen am 25.10.2023